Le Bassin de Skoura-Tazouta (Moyen Atlas, Maroc): Un Exemple de Paléo-Barrage D’âge NéogèneQuaternaire d’origine Tectonique et à Remplissage Fluvio-Lacustre et Travertineux - Fartati, Mohamed El; Hinaje, Said; Amrani, Samir; Gharmane, Youssef; Yaagoub, Driss (European Scientific Journal, ESJ, 2019)
The Tazouta-Skoura subsidiary basin, located in the folded Middle Atlas, corresponds to a collapsed zone with multiphase tectonics in the Neogene and Quaternary; it is limited to the west by a branch of the NMAA (North Middle Atlas Accident) and to the south by the Tichoukt ramp. This basin, interpreted by our predecessors as a simple lake basin, is characterized by fluvio-lacustrine and travertine sedimentary deposits. The palaeogeographic and geodynamic studies (geological mapping, lithostratigraphy, … etc) that we have carried out in the Tazouta-Skoura area allowed us to determine the factors responsible for the genesis and evolution of the neogene-quaternary lake basin of Oued Mdaz palaeo-dam. The tectonic and microtectonic analyses of the brittle formations, that affected the neogene and quaternary deposits and their jurassic basis, allowed us to determine the paleo-field of stresses from the valesian, the miocene, the pliocene until the quaternary age, and to highlight the paleo-geography of the zone in question. These states of tectonic stresses played a key role in the geodynamic, structural and paleogeographic evolution of this basin. The dam wall corresponds to a vallesian N130 normal fault with SW dipping, which inverted the bajocian and bathonian strata to SW. The marly levels of these layers, that have a thickness exceeding tens of meters, constitute an impermeable obstacle which blocked the flow of the surface and infiltration water. The lake of the paleo-dam contains a vallesian clay and carbonnate lacustrine deposits. These deposits are surmounted by marine marls from the upper miocene, fluvial Skoura puddings and lake lime-stones of the pliocene age, as well as quaternary fluvio-lacustrine and travertine deposits. This basin is structured by several families of faults, notably NW-SE, ENE-WSW, NE-SW and N-S. The most recent faults correspond to mid-upper quaternary N 170 normal faults. The normal movements of these sub-meridian faults is responsible for elevation of the Douar Ait Chaib plateau, the dislocation of the natural wall of the paleodam of paleo-Mdaz, and eventually the very fast emptying of the lake. This last phenomenon resulted in fast erosion which left hummocks with horizontal surface (Garas). Le bassin subsidient de Tazouta-Sakoura, situé dans le Moyen Atlas plissé, correspond à une zone effondrée à tectonique polyphasée au Néogène et au Quaternaire, il est limité à l’ouest par une branche de l’ANMA (Accident Nord Moyen Atlasique) et au sud par la rampe de Tichoukt. Ce bassin est interprété par nos prédécesseurs comme un bassin lacustre au sens large et à remplissage sédimentaire fluvio-lacustre et travertineux. Les études paléogéographique et géodynamique (cartographie géologique, lithostratigraphie,…) que nous avons effectuées dans la zone de TazoutaSkoura nous ont permis de déterminer les facteurs responsables de la genèse et de l’évolution de ce bassin lacustre en paléo-barrage de Oued Mdaz d’âge néogène-quaternaire. Les analyses tectoniques et microtectoniques des structures cassantes affectant les dépôts néogènes, quaternaires et leur substratum jurassique, nous ont permis de déterminer les paléo-champs de contraintes d’âge vallésien, miocène supérieur, pliocène et quaternaire. Ces états de contraintes tectoniques ont joué un rôle primordial dans l’évolution géodynamique, structurale et paléogéographique de ce bassin. Le mur du barrage correspond à une faille normale N130 à pendage SW d’âge vallésien, qui a basculé les couches bajociennes et bathoniennes vers le SW. Les niveaux marneux de ces couches constituent un obstacle imperméable qui a bloqué les écoulements des eaux de surface et d’infiltration. Le lac du paléo-barrage a connu une sédimentation lacustre de nature argileuse et carbonatée au Vallésien. Ces dépôts sont surmontés par les marnes d’origine marine du Miocène supérieur, les poudingues de Skoura d’origine fluviatile et les calcaires lacustres du Pliocène, et par les dépôts fluvio-lacustres et travertineux du Quaternaire. L’ensemble est structuré par plusieurs familles de failles : NW-SE, ENE-WSW, NE-SW et N-S. Les failles les plus récentes correspondent aux failles normales de direction moyenne N170 d’âge quaternaire moyen-récent. Le jeu normal de ces failles subméridiennes a provoqué d’une part la surélévation du plateau du Douar Ait Chaib, et d’autre part la dislocation du mur naturel du paléo-barrage sur le paléo-Mdaz et la vidange très rapide du lac. Ce dernier phénomène a provoqué une érosion rapide qui a laissé des buttes témoins à surface horizontale (Garas).